A Combined Study on Degradation Mechanism of Reactive Orange 16 through Fenton‐like Process: Experimental Studies and Density Functional Theoretical Findings. Issue 48 (20th December 2022) - Yildiz, Sayiter; Topal Canbaz, Gamze; Kaya, Savaş; Maslov, Mikhail M.
Abstract: In this study, the removal efficiency of Reactive orange 16 (RO16) azo dyes from aqueous solution with different Fenton reactions (Fenton/photo‐Fenton/sono‐Fenton/ sono‐photo‐Fenton) were investigated. For optimum conditions, the effects of variables such as H2 O2, Fe 2+, reaction time, pH and dye concentration on the oxidation process were investigated. In addition, the interaction between Fenton reagents and the dye molecule was revealed by Density Functional Theory (DFT) calculations. Important quantum chemical parameters reflecting the reactivity of the studied dye were calculated. Effective RO16 degradation was achieved by Fenton oxidation at conditions of 100 mg L −1 H2 O2, 10 mg L −1 Fe 2+, 100 mg L −1 dye concentration, 3 pH and 30 minutes. While the degradation efficiency with Fenton process was 97.77 %, it reached 98.78 %, 98.31 % and 98.22 % when UV−A, UV−B and UV−C lights were applied respectively. In the sono‐Fenton process application, the degradation efficiency was determined as 97.96 %. The degradation of RO16 by sono‐photo‐Fenton was 96.12 %, 96.13 % and 96.83 % under different lamps (UV−A, UV−B and UV−C), respectively. In addition, in the kinetic study, it was determined that each process complies with the zeroth‐order kinetics. To see the nature and power of the interaction between hydroxyl radical and RO16, important quantum chemical parameters of Conceptual Density Functional Theory were calculated and their effects on degradation process were discussed as detailed. Degradation mechanism was highlighted in the light of DFT calculations. Abstract : In this study, the removal efficiency of RO16 azo dyes from aqueous solution with different Fenton reactions were investigated. In addition, the interaction between Fenton reagents and the dye molecule was revealed by DFT calculations. Fenton like processes can be considered as a promising and effective method for removing the dye from water. DFT calculations performing to see the degradation mechanism supported the experimental observations.